The Relationship between Financial Reporting Practices and the 1986 Alternative Minimum Tax - Wang, Shiing-Wu (The Accounting Review, 1994)
[As examined in previous research (e.g., Gramlich 1991; Dhaliwal and Wang 1992), accounting accruals related to the alternative minimum tax (AMT) may either contain effects unrelated to the book income adjustment or be confounded by other changes in the 1986 Tax Reform Act. For example, total accruals in Gramlich (1991) arising from changes in accounts receivable and inventory have no effect on the book income adjustment because they affect taxable income and book income simultaneously.1 Also, the repeal of the investment tax credit and a slower capital recovery schedule in the 1986 Tax Reform Act may induce firms to reduce investment. This change may decrease depreciation (a component of accruals in Gramlich (1991)) and the depreciation timing difference (a component of accruals in Dhaliwal and Wang (1992)) in 1987 and may contribute to the observed results.2 Prior research also relied on pre-1987 data and certain assumptions to predict the likelihood that firms would be subject to the AMT in 1987 (see Gramlich (1991) and Dhaliwal and Wang (1992) for examples). Such an approach is warranted only under an assumption of no change in tax status for the sample firms. However, the overwhelming changes instituted by the 1986 Tax Reform Act make such an assumption questionable. Misclassification of firms can lead to results attributable to sample partition rather than the AMT. Furthermore, firms with low tax payments are classified as the AMT firms in these studies. Since low tax payments may be an indication of poor financial condition, the AMT sample is likely to contain firms with deteriorating financial condition which may lead to an overall decrease in accruals in 1987. This study improved three aspects of previous research designs to test the effect of the book income adjustment on financial reporting. First, the sample consisted of firms that were indeed subject to the AMT in 1987 to ensure that only the behavior of AMT firms were examined. Second, only accrued expenses and revenues that were not sensitive to other major changes in the 1986 tax law were assessed. Third, a time-series model controlling for changes in firms' financial condition was used to estimate the unexpected accruals. In general, the results indicated that firms that were subject to the AMT in 1987 exhibited unusual shifts in accounting accruals in 1986 and 1987. Unlike the institution of the AMT in 1987, the repeal of the book income adjustment in 1990 was independent of other major changes in tax law, providing a rather clean event to examine the effect of the book income adjustment on financial reporting. Evidence of accruals shifting for firms subject to the AMT in 1989 would lend further support to the conclusion that the AMT affects financial reporting practices. Accordingly, accruals of sample firms subject to the AMT in 1989 were examined. An unusual shift in accounting accruals was observed in 1989 but in a direction opposite to the 1987 sample.]